2007
DOI: 10.1016/j.trstmh.2006.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple interventions on community health workers’ adherence to clinical guidelines in Siaya district, Kenya

Abstract: Evaluation of a community health worker (CHW) programme in Siaya district, Kenya, showed CHWs commonly made errors in managing childhood illness. We assessed the effect of multiple interventions on CHW healthcare practices. A sample of 192 ill-child consultations performed by 114 CHWs in a hospital outpatient department between February and March 2001 were analysed. The mean percentage of assessment, classification and treatment procedures performed correctly for each child was 79.8% (range 13.3-100%). Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 29 publications
6
81
1
Order By: Relevance
“…With an average of 6 min per supervisory visit spent discussing performance compared to 59 min spent collecting service statistics, the authors hypothesize that supervision quality was poor and therefore reduced frequency did not affect worker performance (44). Five multivariate analyses explored the association between supervision frequency and health worker (6466) or CHW (67, 68) performance in low-income countries; only two found a positive association (64, 68). There was no association between midwife performance scores and supervision frequency in the control group of a study in the Philippines but there was a dose response in the intervention group with improved supervision suggesting that increased frequency only improves performance if quality supervision is in place (37).…”
Section: Resultsmentioning
confidence: 99%
“…With an average of 6 min per supervisory visit spent discussing performance compared to 59 min spent collecting service statistics, the authors hypothesize that supervision quality was poor and therefore reduced frequency did not affect worker performance (44). Five multivariate analyses explored the association between supervision frequency and health worker (6466) or CHW (67, 68) performance in low-income countries; only two found a positive association (64, 68). There was no association between midwife performance scores and supervision frequency in the control group of a study in the Philippines but there was a dose response in the intervention group with improved supervision suggesting that increased frequency only improves performance if quality supervision is in place (37).…”
Section: Resultsmentioning
confidence: 99%
“…This finding may to a great extent explain the overall poor performance of CHWs because they need regular training in order to maintain a good level of knowledge and skills (25–28). It is therefore important to hold regular refreshment training for CHWs to ensure good job performance.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from this small number of studies is also mixed. Some found positive associations between quality of care and training [55,56] and supervision [56], while others showed no significant associations with training [57,58] or supervision [58]. Two recent studies in Ethiopia showed associations between supportive supervision [59] and PRCMM [60] and improved consistency in iCCM patient registers between HEWs’ assessment, classification, and treatment of sick children.…”
Section: Discussionmentioning
confidence: 99%